Investimentos, financiamento e cooperaç\~ao do Brasil em Angola e Moçambique: Evoluç\~ao dos dados e um balanço dos efeitos do acordo de cooperaç\~ao e facilitaç\~ao de investimentos - Ana Saggioro Garcia; Rodrigo Curty Pereira; Maria Eduarda Lopes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Our research aims to analyze Brazil's role in the international investment regime and to assess the effects of the Agreement on Cooperation and Investments Facilitation (ACIF) on Brazilian investments in Angola and Mozambique. In this second Discussion Paper, we discuss the relations between Brazil and Angola, and Brazil and Mozambique, through an interrelated approach of what we call the tripod investment, financing and cooperation. We begin with an overview of Brazil-Africa relations since the 2000s, seeking to show that, after the boost given during the Lula da Silva government, there was a continuous drying up of resources for financing and cooperation with African countries, and a narrowing of objectives to a greater emphasis on trade and investment, and a greater focus on defense cooperation. Following the tripod, we went into more detail on Brazil's relations with Angola and Mozambique in terms of trade and investment, credit and financing, as well as technical cooperation and development aid. Our analysis was intended to update previous research and give the most recent picture of the political, economic and social conjuncture in which Brazilian investments take place. Finally, we provide a review of the interviews conducted with key players in Angola and Mozambique. The interviews sought to extract their analyses and perspectives on the economic development processes in each of their countries, the role of foreign direct investment, and the effects of investment facilitation and protection agreements, situating the ACIF and relations with Brazil in this scenario. Although the ACIF is seen as a less restrictive model than the traditional bilateral investment treaties, we find evidence that it is not sufficient to promote investments between the countries involved. For this, it would be necessary to ensure a stable economic and political environment for investors both in Brazil and in Angola and Mozambique, and to resume economic diplomacy for a better exchange of experiences and mutual knowledge.
10419/284913
Keywords: F53; F55; O55; 330; Angola; Mozambique; ACFI; foreign direct investment; cooperation; credit and financing